Pore Size Modulation in Flexible Metal‐Organic Framework Enabling High Performance Gas Sensing - Wang, Chuan‐Zhe; Chen, Jie; Li, Qiao‐Hong; Wang, Guan‐E; Ye, Xiao‐Liang; Lv, Jia; Xu, Gang (Angewandte Chemie International Edition, 2023)
Pore size plays a critical role in determining the performance of metal‐organic frameworks (MOFs) in catalysis, sensing, and gas storage or separation. However, revealing the pore‐size/property relationship remains extremely challenging because ideal structure models possessing different pore sizes but having the same components are lacking. In this work, a solvent‐coordination directed structure swelling method was developed for modulating the ratio between the large and narrow pore phases of a flexible MOF, MIL‐88B. Pore‐size‐dependent gas sensitivity and selectivity were studied for the first time in the MIL‐88B samples. The optimized MIL‐88B‐20 % sample showed one of the best sensing performances among all the reported MOF‐based H2S‐sensing materials. This work not only provides a method to synthesize ideal structure models for revealing the relationship between pore‐size and properties, but also may inspire the development of high‐performance gas sensing materials. The solvent‐coordination directed structure swelling method was used to modulate the pore size of MIL‐88B, which enables to reveal the pore‐size‐dependent gas sensitivity and selectivity of MOF materials for the first time.